Insights into Orris (Iris pallida Lam.) In Vivo Acclimatization and Response to Salt Stress via Exogenous Melatonin Application - Annalisa Meucci; Cristina Ghelardi; Rita Maggini; Fernando Malorgio; Beatrice Pezzarossa; Irene Rosellini; Anna Mensuali (Agriculture)
The loss of agricultural land is one of the main problems facing the global agricultural sector, and it is related to multiple phenomena; one of the main causes is soil salinization, induced both by natural processes and human activities. Among the strategies adopted to deal with soil salinization and its mitigation, the cultivation of species able to survive in saline soils seems to be an effective way of making salt-compromised lands usable. Iris pallida is a rustic plant and a species of high economic value that is mostly cultivated for perfume production. Consequently, the application of I. pallida to cover soils not suitable for crops traditionally cultivated for human and livestock nutrition could be considered; therefore, a preliminary test on the capacity of I. pallida to tolerate salinity during the acclimatization phase of micropropagated plants was conducted. Plantlets were treated with exogenous melatonin during the in vitro phase by adding it to the culture medium; therefore, during the acclimatization phase, crescent salt doses (150, 300, and 400 mM) were added to the soil every 14 days, administering melatonin to plants by a spray solution 24 h before each salt addition. At the end of the experiment, biometric measurements, chlorophylls, carotenoids, and macro-element contents were measured, and the relative water content (RWC) was determined in each salt addition. The results showed that orris plants can survive soil salt concentrations of up to 400 mM, and that the 50 µM melatonin spray treatment can protect orris rhizomes from salt side effects.